Genotoxicity and cytotoxicity of glass ionomer cements on Chinese hamster ovary (CHO) cells - Ribeiro, D. A.; Marques, MEA; Salvadori, Daisy Maria Favero [UNESP] (Springer, 2006)
Glass ionomer cements are widely used in dentistry as restorative materials and adhesives for composite restorations. However, the results of genotoxicity studies using these materials are inconclusive in literature. The goal of this study was to examine the genotoxic and cytotoxic potential of three different glass ionomer cements available commercially (Ketac Cem, Ketac Molar and Vitrebond) by the single cell gel (comet) assay and trypan blue exclusion test, respectively. For this, such materials were exposed to Chinese hamster ovary (CHO) cells in vitro for 1 h at 37 degrees C. Data were assessed by Kruskall-Wallis nonparametric test. The results showed that the powder from Ketac Molar displayed genotoxicity only in the maximum concentration evaluated (100 mu g/mL). In the same way, the liquid from Vitrebond at 0.1% dilution caused an increase of DNA injury. Significant differences (P < 0.05) in cytotoxicity provoked by all powders tested of glass ionomer cements were observed for exposure at 1000 mu g/mL concentration. With respect to liquids of glass ionomer cements evaluated, the major toxic effect on cell viability was produced at 10%, beginning at the dilution of 0.5% for Vitrebond. Taken together, we conclude that some components of glass ionomer cements show both genotoxic and cytotoxic effects.